2020
DOI: 10.1029/2020wr028066
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Managing Large‐Scale Geochemical Impacts From Groundwater Replenishment With Highly Treated Reclaimed Wastewater

Abstract: Reuse of wastewater through a combination of advanced wastewater treatment (AWT) and managed aquifer recharge (MAR) is an important water management option. As an integral part of any AWT-MAR system, the geochemical compatibility of the recharged water with the targeted aquifer must be assessed to avoid groundwater quality deterioration. Although short-term field experiments may uncover potentially concerning sediment-water disequilibria, an advanced analysis is often required to understand the long-term geoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 60 publications
(143 reference statements)
3
16
0
Order By: Relevance
“…However, the water quality shifts observed under batch conditions were expected to be less pronounced during field-scale operations due to (1) oxygen supply to the aquifer being limited in injection water compared to continuous replenishment in the laboratory experiment, (2) mixing of waters from different aquifer zones, (3) prevention of metal accumulation by flushing of injection water, and (4) sediment buffering and resorption down gradient. 70,142 Later, field-scale MAR operations in the same aquifer showed that sufficient pH buffering occurred, predominantly by proton buffering at exchange sites, 143,144 and metals mobilization was not a significant concern. 144 If recharge water introduces competitive ions, contaminant desorption and mobilization can occur from sorption sites associated with Fe (oxyhydr)oxides or other minerals.…”
Section: Mechanisms Of Contaminant Mobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the water quality shifts observed under batch conditions were expected to be less pronounced during field-scale operations due to (1) oxygen supply to the aquifer being limited in injection water compared to continuous replenishment in the laboratory experiment, (2) mixing of waters from different aquifer zones, (3) prevention of metal accumulation by flushing of injection water, and (4) sediment buffering and resorption down gradient. 70,142 Later, field-scale MAR operations in the same aquifer showed that sufficient pH buffering occurred, predominantly by proton buffering at exchange sites, 143,144 and metals mobilization was not a significant concern. 144 If recharge water introduces competitive ions, contaminant desorption and mobilization can occur from sorption sites associated with Fe (oxyhydr)oxides or other minerals.…”
Section: Mechanisms Of Contaminant Mobilizationmentioning
confidence: 99%
“…70,142 Later, field-scale MAR operations in the same aquifer showed that sufficient pH buffering occurred, predominantly by proton buffering at exchange sites, 143,144 and metals mobilization was not a significant concern. 144 If recharge water introduces competitive ions, contaminant desorption and mobilization can occur from sorption sites associated with Fe (oxyhydr)oxides or other minerals. This was observed in Bolivar, Australia, during an ASR trial, where phosphate in the injectant limited the amount of As adsorption on Fe (oxyhydr)oxides during injection, while reductive dissolution of Fe (oxyhydr)oxides caused As mobilization during the storage and recovery phases.…”
Section: Mechanisms Of Contaminant Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The referenced studies investigated only the potential of SDW for clean water recharge. In practice, however, storm water (Page et al 2010;Gao et al 2014), water from ephemeral rivers (Alataway and El Alfy 2019), and treated waste water (Goren et al 2014;Sun et al 2020) are used for MAR. While storm waters contain high loads of suspended particles, treated waste waters are usually characterized by high concentrations of nutrients, bacteria, and dissolved organic matter (Icekson-Tal et al 2003;Asano and Cotruvo 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since the design of the grid is very flexible, the grid refinement is no longer restricted by the shape grid and refinement area. Multi-scale models can be constructed by the USG method either when the boundary of the local model area is irregular or the hydrological stresses change in the local area might have a significant influence on the larger region [19,20]. Finer grid resolution can be used to refine the area near river channels [21,22] or only on the model top layer [23] to investigate surface and groundwater interaction.…”
Section: Introductionmentioning
confidence: 99%